Influence of the Soil-Water Retention Curve Models on the Stability of Residuals Soils Slope - Agus Setyo Muntohar (Himpunan Ahli Teknik Tanah Indonesia, 2015)
The study is focused on the investigation of effect the characterization of SWRC model and its effect on the slope stability on a simple infinite slope. The SWRC models were fitted to the laboratory test using mini tensiometer and filter paper. In particular, four unimodal SWRC models were evaluated for comparison in this study, i.e. van Genuchten model (VG), modified van Genuchten model (MVG), Brooks- Corey model (BC), and Kosugi log-normal model (KLN). The slope stability analysis was conducted in terms of Factor of Safety (FS) by applying the infinite slope model incorporating infiltration model. The infiltration model was analyzed by Richard’s one-dimensional infiltration equation. The analysis resulted that The VG and KLN models produced lower estimation of safety factor than BC and MVG models. The distribution of pore water pressure varied with the SWRC models. Hence, different SWRC model contribute different FS values. The results indicate that the SWRC model shall be applied carefully since the model will have a different conclusion to the slope instability.